Public management in municipalities: Research trends using bibliometric indicators - Alvarez Ushiñahua, Washinton Americo (2025)
Objective. This article identifies research trends in public management within municipalities through a bibliometric analysis. Design/Methodology/Approach. This is a bibliometric study using Scopus as a source for extracting scientific literature. For this purpose, indicators of productivity, impact, and thematic analysis are used. Results/Discussion. The analysis of scientific production in public management reveals an exponential growth since 2000, with a marked increase from 2017, reaching its maximum in 2022 (41 publications). In addition, the ten most cited papers addressing topics such as organizational capacity, leadership, new public management (NPM), and e-government were identified. These papers coincide in pointing out that the organizational context and institutional characteristics are determinants in the impact of administrative reforms. Peru is poised to emerge as a key case study in 2024, with a focus on municipal management and local development. The most recurrent themes include efficiency in public services, NPM reforms, open innovation, and the role of e-government, evidencing a multidisciplinary research approach. Conclusions. Publication practices in municipal public management are primarily carried out in specialized journals with a distinct local character. Meanwhile, the most recent research trends on the subject range from the use of ICTs to the work strategies of governments and decision-makers, in response to complex moments in decision-making.